If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-3x=2(x+3)
We move all terms to the left:
-3x-(2(x+3))=0
We calculate terms in parentheses: -(2(x+3)), so:We get rid of parentheses
2(x+3)
We multiply parentheses
2x+6
Back to the equation:
-(2x+6)
-3x-2x-6=0
We add all the numbers together, and all the variables
-5x-6=0
We move all terms containing x to the left, all other terms to the right
-5x=6
x=6/-5
x=-1+1/5
| |k+1|=1 | | 4x-2(x-4)=-6+5x+8 | | 4+1+8a+8a=4a-5+7a | | n-18=19 | | 7+2n=7n-8 | | x/9+13=0 | | -7(k+9)=9(k+-5)+-14k | | 8-4(f-3)=0 | | -7(k+9)=9(k+-5)-14k | | 5+7x+x=1+7x+1 | | 14n=-126 | | -7(x+6)-3(3x-3)=-65 | | 9k-16=52 | | g+143=1000 | | 33/4=r=1/8 | | №23x=10 | | 4z-3(z-6)=3=2z | | -4m-8=54 | | 2-2m=-20 | | 14-x=4+2x | | 21=-7×n | | 28j=952 | | 95x-15=-12 | | -27d=270 | | -8(8x-7)=440 | | 4^5x-9=(1/27)^2x-8 | | 5(3-e)+10=0 | | h+577=952 | | 8/11n=64 | | X=1+1.2x | | -10k+6k+k×10=60 | | 8/11n=74 |